Rabies in Iran - Baghaipour, M. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a disease caused by a virus, Lyssavirus rabies that affects the nervous system and usually results in death unless treated quickly. Rabies is found in mammals in all regions of the world. The disease infects domestic and wild animals, and is spread to people through close contact with infected saliva via bites or scratches. Dogs are the main host and transmitter of rabies but bats, foxes, raccoons, coyotes, wolves may transmit the disease as well. More than 50 000 people die of rabies every year. The virus spreads through the central nervous system and progressive, fatal inflammation of the brain and spinal cord develops. After an incubation period of 1–3 months (days to years) the initial symptoms start with fever and often pain or paraesthesia at the wound site. In about 35% of the patients, Rabies has a longer course .The muscles gradually become paralyzed, starting at the site of the bite or scratch. A coma slowly develops, and eventually death occurs. It is named the paralytic form and its diagnosis is difficult. The majority of patients show a furious form and exhibit signs of hyperactivity, excited behavior, hydrophobia and sometimes aerophobia. After a few days, death occurs by cardio-respiratory arrest. No tests are available to diagnose rabies infection in humans before the onset of clinical disease. For suspected animals, taking tissue samples (often brain tissue) and using immunofluorescence or immunological techniques to detect the virus is the mainstay of diagnosis. A person exposed to rabies should ideally be treated within 12 hours of the exposure and definitely within 48 hours for the best outcome. They are usually treated with rabies immune globulin and rabies vaccine initially and then get several additional vaccine injections. The number of infected person has been decreased during past decade in Iran. Most of them are males and under ten years old. More than 250 centers provide post exposure treatment for Rabies and Pasture Institute have produced IG and Vaccine of Rabies since 85 years ago.